THE EFFECT OF USING CONTEXT CLUES IN ENHANCING STUDENTS’ VOCABULARY BUILDING THROUGH A READING TEXT AT SMPN 52 MAKASSAR - Maria Frederika Jamrewav; Hj. St. Haliah Batau; Ulfah Syam (Lembaga Jurnal FKIP Universitas Bosowa, 2021)
The objective to find out the effect of using context clues in in enhancing students vocabulary building through reading text at SMPN 52 Makassar.The writer used instrument; it is a reading and vocabulary test that given (pre-test and post-test). The pre-test was used to find out data about the recognition and understanding of students’ vocabulary before implementing the context clues strategy and the post-test was carried out to find out data about the introduction and understanding of students' vocabulary after implementing the context clues strategy. The method used in this study is a pre-experiment using one class. The population in this study were all students of class VIII-DSMPN 52 Makassar, totally 28 students, so the writer took a purposive sampling technique. In addition, to analyse the data, writer used SPSS 21. The results showed that the increase in students' vocabulary recognition increased on all indicators of word recognition, such as identifying clues in multiple choice (69.23% progress) and finding word meanings (43.02% progress). The results of this study finally showed that the students' vocabulary understanding was 53.00 for their pre-test and 81.64 for their post-test. This fact shows that the students’ score in the post-test is higher than the pre-test score. It can be concluded that vocabulary learning with the context clues strategy was effective in improving vocabulary VIII-D SMPN 52 Makassar.